2020
DOI: 10.1038/s41598-020-76685-z
|View full text |Cite
|
Sign up to set email alerts
|

311 service requests as indicators of neighborhood distress and opioid use disorder

Abstract: Opioid use disorder and overdose deaths is a public health crisis in the United States, and there is increasing recognition that its etiology is rooted in part by social determinants such as poverty, isolation and social upheaval. Limiting research and policy interventions is the low temporal and spatial resolution of publicly available administrative data such as census data. We explore the use of municipal service requests (also known as “311” requests) as high resolution spatial and temporal indicators of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…29 Similarly, Li et al found that the location of 311 municipal service calls in Columbus, OH was associated with opioid overdose geographic hotspots. 33 A study conducted in Texas used a combination of data from emergency room visits, the Youth Risk Behavior Survey, poison control cases, and qualitative interviews to characterize a "cheese" heroin use outbreak. 31 Another study implemented in Kentucky used data from a combination of death certificates, overdose deaths from the State Medical Examiners' Office, emergency room visits, and prescription drug monitoring programs to detect potential opioid use clusters at state level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Similarly, Li et al found that the location of 311 municipal service calls in Columbus, OH was associated with opioid overdose geographic hotspots. 33 A study conducted in Texas used a combination of data from emergency room visits, the Youth Risk Behavior Survey, poison control cases, and qualitative interviews to characterize a "cheese" heroin use outbreak. 31 Another study implemented in Kentucky used data from a combination of death certificates, overdose deaths from the State Medical Examiners' Office, emergency room visits, and prescription drug monitoring programs to detect potential opioid use clusters at state level.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing this information with epidemiological surveillance data, including poison call center data, as well as data from substance use treatment and harm reduction organizations can further minimize time to outbreak detection. 28,33 Substance use behavioral surveillance had until recently been grounded on routine population surveys such as the NSDUH, as well as opioid prescription and OUD treatment records.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the 2020 US Census becomes available, we would like to extend our synthetic population dataset to comprise all the US population. Currently, the synthetic population did not comprise financial, employment or educational backgrounds, with such data, the synthetic population could be potentially used by an agent-based modeler wanting to explore issues such as residential location or public health issues (e.g., Jiang et al, 2021;Li et al, 2020). This could be remedied by adding additional variables to the agents from the census dataset.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Li et al. (2020) used an inhomogeneous cross‐K function to examine the pattern between 311 data and opioid overdose event data. Besides, they applied hotspot analysis (Getis‐Ord Gi* statistic) to determine the location of data clusters at the census block level.…”
Section: Materials and Backgroundmentioning
confidence: 99%
“…The developed system includes heat maps to represent the intensity of reports at geographical points and the application of density-based and hierarchical clustering to visualize groupings of reports at different granularity levels. Li et al (2020) used an inhomogeneous cross-K function to examine the pattern between 311 data and opioid overdose event data. Besides, they applied hotspot analysis (Getis-Ord Gi* statistic) to determine the location of data clusters at the census block level.…”
Section: Spatial Analysis: Moran's Imentioning
confidence: 99%